Karakteristik Populasi Ansonia spinulifer (Mocquard, 1890) di Bukit Wangkang Kecamatan Kubu Kabupaten Kubu Raya (Universitas Negeri Semarang, 2022)
Borneo is one of the centers of amphibian diversity. The distribution of amphibians in Borneo can be seen from the variety of species in lowland forest areas, rice fields, and along rivers. A. spinulifer is the species which is one of the endemic species to the island of Borneo. This study aims to examine the population character of A. spinulifer in the Wangkang Hill area which can be used as a consideration in the management of amphibian species in Borneo. Sample is collected in Bukit Wangkang, Kubu District, Kubu Raya Regency. The research method used is the Visual Encounter Survey (VES) combined with line transects. The population density of A. spinulifer in the Wangkang hill area, Kubu District, Kubu Raya Regency is 0.426 individuals/m2, The sex ratio of male and female A. spinulifer is 1:1, the gonad maturity level of female and male A. spinulifer is at level II-IV Fecundity of female A. spinulifer is 235-639 eggs. Kalimantan merupakan salah satu pusat keanekaragaman jenis amfibi. Sebaran amfibi di Kalimantan dapat dilihat dari keanekaragaman jenisnya di kawasan hutan dataran rendah, persawahan, dan di sepanjang sungai. A. spinulifer merupakan salah satu spesies endemik pulau Kalimantan. Penelitian ini bertujuan untuk mengkaji karakter populasi A. spinulifer di kawasan Bukit Wangkang yang dapat dijadikan pertimbangan dalam pengelolaan jenis amfibi di Kalimantan. Pengambilan sampel dilakukan di Bukit Wangkang, Kecamatan Kubu, Kabupaten Kubu Raya. Metode penelitian yang digunakan adalah Visual Encounter Survey (VES) yang dipadukan dengan transek garis. Kepadatan populasi A. spinulifer di kawasan Bukit Wangkang, Kecamatan Kubu, Kabupaten Kubu Raya adalah 0,426 individu/m2, rasio jenis kelamin A. spinulifer jantan dan betina 1:1, tingkat kematangan gonad betina dan jantan A. spinulifer berada pada level II-IV dengan kisaran indeks kematangan gonad rata-rata 0,30-0,90%. Fekunditas A. spinulifer betina rata-rata 235-639 butir telur. Keywords: Amphibi, Ansonia spinulifer, Density, Sex Ratio, Gonad Maturity Level